2002
DOI: 10.2458/azu_jrm_v55i1_gentner
|View full text |Cite
|
Sign up to set email alerts
|

Classifying federal public land grazing permittees

Abstract: This study identifies the characteristics and attitudes of public land ranchers. Data from a random survey of 2,000 U.S. Forest Service and Bureau of Land Management grazing permittees (53.5% response rate) were cluster analyzed and 8 distinct groups of ranchers were identified. Each cluster differed with respect to why they were in ranching and how they would respond to public land policy changes related to grazing fees, grazing reductions, and changes in grazing season. Profit motivation for being in ranchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 6 publications
1
50
0
Order By: Relevance
“…Because this will change ecosystem characteristics through the cessation of grazing, it will likely change the ecosystem services produced at the ranch and pasture levels, but ultimately also at the landscape level, especially given the uncertainty about whether or not a new generation of ranchers will hold the same amenity values and continue to fund them (Brunson and Huntsinger 2008). Across the western United States, multiple studies have shown that most ranching families subsidize their ranches with off-ranch income (Smith and Martin 1972, Gentner and Tanaka 2002, Huntsinger et al 2010b. As discussed by Oviedo et al (2012), the decline of commercial production could eventually lead to the subdivision of ranches, implying a potential threat from subsequent habitat and http://www.ecologyandsociety.org/vol19/iss1/art8/ landscape fragmentation.…”
Section: The Landscape Scalementioning
confidence: 99%
“…Because this will change ecosystem characteristics through the cessation of grazing, it will likely change the ecosystem services produced at the ranch and pasture levels, but ultimately also at the landscape level, especially given the uncertainty about whether or not a new generation of ranchers will hold the same amenity values and continue to fund them (Brunson and Huntsinger 2008). Across the western United States, multiple studies have shown that most ranching families subsidize their ranches with off-ranch income (Smith and Martin 1972, Gentner and Tanaka 2002, Huntsinger et al 2010b. As discussed by Oviedo et al (2012), the decline of commercial production could eventually lead to the subdivision of ranches, implying a potential threat from subsequent habitat and http://www.ecologyandsociety.org/vol19/iss1/art8/ landscape fragmentation.…”
Section: The Landscape Scalementioning
confidence: 99%
“…Drawing on questionnaires of Liffman et al (2000), Gentner (1999), Smith and Martin (1972), and Bartlett et al (1989), the authors constructed a survey exploring motivations for staying in ranching versus leaving ranching. The survey was pre-tested on ranchers in Larimer County, Colo.…”
Section: Rancher Surveymentioning
confidence: 99%
“…Some variables were deemed to be not diagnostic and were excluded in accordance with previous studies (Rosenberg and Turvey 1991;Gentner and Tanaka 2002;Köbrich et al 2003;Ruiz et al 2008). For example, geographic location was omitted to allow for testing if farm types occurred across regions.…”
Section: Variable Selection and Principal Component Analysismentioning
confidence: 99%
“…Typologies of North American livestock production systems are rare, but several studies have demonstrated the importance of organizing farms into homogeneous categories (e.g., Rosenberg and Turvey 1991;Agriculture and Agri-Food Canada (AAFC) 2002;McBride and Mathews 2011). In the United States, Gentner and Tanaka (2002) identified eight clusters of cattle and sheep ranchers based on their attitude and attributes about the farm business: values that defined social and economic characteristics of farm households (Barlett 1986).…”
Section: Introductionmentioning
confidence: 99%